Biochemical and microstructural characteristics of collagen biopolymer from unicornfish (Naso reticulatus Randall, 2001) bone prepared with various acid types - Nurul Syazwanie Fatiroi; Abdul Aziz Jaziri; Rossita Shapawi; Ruzaidi Azli Mohd Mokhtar; Wan Norhana Md. Noordin; Nurul Huda (MDPI, 2023)
Biopolymer-like collagen has great industrial potential in terms of its excellent properties, such as strong biocompatibility, high degradability, and low antigenicity. Collagen derived from fish by-products is preferable as it is safer (free from transmittable diseases) and acceptable to most religious beliefs. This study aimed to characterize the unicornfish (Naso reticulatus Randall, 2001) bone collagens prepared with different type of acids, i.e., acetic acid, lactic acid, and citric acid. A higher yield (Y) (p < 0.05) was obtained in the citric-acid-soluble collagen (CASC) (Y = 1.36%), followed by the lactic-acid-soluble collagen (LASC) (Y = 1.08%) and acetic-acid-soluble collagen (AASC) (Y = 0.40%). All extracted collagens were classified as type I due to the presence of 2-alpha chains (α1 and α2). Their prominent absorption spectra were located at the wavelengths of 229.83 nm to 231.17 nm. This is similar to wavelengths reported for other fish collagens. The X-ray diffraction (XRD) and infrared (IR) data demonstrated that the triple-helical structure of type I collagens was still preserved after the acid-extraction process. In terms of thermal stability, all samples had similar maximum transition temperatures (Tmax = 33.34–33.51 ◦C). A higher relative solubility (RS) of the unicornfish bone collagens was observed at low salt concentration (0–10 g/L) (RS > 80%) and at acidic condition (pH 1.0 to pH 3.0) (RS > 75%). The extracted collagen samples had an irregular and dense flake structure with random coiled filaments. Overall, bones of unicornfish may be used as a substitute source of collagen.